OSSE quantitative assessment of rapid‐response prestorm ocean surveys to improve coupled tropical cyclone prediction. Issue 7 (17th July 2017) - Halliwell, G. R.; Mehari, M.; Shay, L. K.; Kourafalou, V. H.; Kang, H.; Kim, H.‐S.; Dong, J.; Atlas, R.
Abstract: Ocean fields that initialize coupled TC prediction models must accurately represent the dynamics of mesoscale features and the associated distribution of upper ocean temperature and salinity. They must also provide unbiased realizations of upper ocean heat content and stratification. Ocean Observing System Simulation Experiments (OSSEs) are performed for three storms: Isaac, 2012; Edouard, 2014; and Gonzalo, 2014. These OSSEs assess the impact of rapid‐response prestorm ocean profile surveys on improving ocean model initialization. Two types of surveys are evaluated: airborne deployments of expendable profilers and deployments of in situ thermistor chains along lines intersecting predicted storm paths. Assimilation of the existing ocean observing system substantially constrains mesoscale structure in dynamical fields, primarily because of the four available altimeters. However, these observations only modestly constrain mesoscale structure and bias in upper ocean thermal fields. Adding rapid‐response airborne surveys to these observing systems produces substantial additional correction in thermal fields, but minimal additional correction in dynamical fields. Without altimetry assimilation, rapid‐response profiles produce large additional correction in both dynamical and thermal fields. Airborne CTDs sampling temperature and salinity over 1000 m versus XBTs sampling temperature over 400 m produce additional correction for dynamical fields, but not for upper ocean thermal fields. Airborne surveys are generally more effective than thermistor chain deployments because they can sample a larger area at higher horizontal resolution and because the latter only measures temperature over the upper ∼100 m. Both airborne profile surveys and thermistor chain deployments effectively reduce upper ocean thermal biases. Key Points: Perform ocean observing system simulation experiments to evaluate impacts of ocean observations Prestorm ocean profile surveys reduce mesoscale errors and bias in ocean analyses used to initialize coupled TC prediction models